Implementasi Aplikasi Chatbot Informasi Pelayanan Kelurahan Keputih, Surabaya - Edelani, Renovita; Satriyanto, Edi; Nadhori, Isbat Uzzin; Susetyoko, Ronny; Barakbah, Aliridho; Karlita, Tita; Muliawati, Tri Hadiah; Fadliana, Alfi; Maulana, Wahyu Ikbal; Insani, Fawzan; Fauzi Nafi'Ubadah, Kriza; Haikal Yuniarta Krisgianto, Ricko; Saputra, Muhammad Krisnanda Vilovan; Ridho, Bistiana Syafina; Ni'Ma, Najma Akmalina; Damayanti, Anita; Febrianto, Ardiansyah Indra; Alde, Muhammad Riski (El-Mujtama: Jurnal Pengabdian Masyarakat, 2025)
In today's era of digital transformation, the government, particularly Kelurahan Keputih, is aware of the community's need for information regarding the management of kependudukan and non-kependudukan documents. Given their busy lifestyles, residents require a medium to access information related to these matters. This service information is needed to improve bureaucratic efficiency, accelerate information access, and reduce the burden of manual administrative work. Therefore, researchers have developed an AI-based Intelligent Chatbot application using Large Language Modeling (LLM) technology to assist both employees and residents of Kelurahan Keputih in obtaining information related to the management of kependudukan and non-kependudukan services. The implementation of this Chatbot utilizes the Hugging Face library and the LangChain model, one of the Llama models developed by Meta. This Kelurahan Keputih Service Information Chatbot application is named "BambuBot". This application benefits the residents of Keputih by providing them with interactive, comprehensive, and easily accessible information regarding services for managing kependudukan and non-kependudukan documents, as well as platforms for processing these documents.